Clinicopathological and Immunohistochemical Study of Head and Neck Langerhans Cell Histiocytosis from Latin America - Bedran, Natália Rocha (Head Neck Pathol, 2017)
Langerhans cell histiocytosis (LCH) is an inflammatory myeloid neoplastic proliferation with variable clinical behavior caused by the accumulation of CD1a(+)/CD207(+) histiocytes, associated with a variable number of eosinophils, lymphocytes, plasma cells and multinucleated giant cells, most commonly observed in male children. LCH is uncommon in the head and neck region, occurring as ulcerated and reddened plaques or nodules that cause destruction of adjacent soft tissues and bone. The exact etiology of LCH is still unknown and controversial, with possible etiologic role of viruses, including Epstein–Barr virus (EBV). The aim of this study was to describe the clinicopathologic and immunohistochemical features of patients with LCH of the head and neck region. Clinical data from 19 patients with LCH were obtained from the archives of the Federal University of Rio de Janeiro and the Clinical Head and Neck Center of Guatemala. All cases were submitted to morphological, immunohistochemical analysis with CD1a, CD207, CD3, CD20, CD68, S-100 and Ki-67 and in situ hybridization for EBV. Ten cases were female and 9 male, with mean age of 11.5 years. Fourteen cases were located in the oral cavity, three cases in lymph nodes, and two cases in the scalp. In regard to the oral lesions, 13 cases were intra-osseous with six cases in anterior mandible, five cases in posterior mandible, and two cases in posterior maxilla while one case was located exclusively in the gingiva. The inflammatory pattern showed variation in the number of plasma cells, eosinophils and lymphocytes, while tumor cells were positive for CD1a, S-100 and CD68 in all cases, and positive for CD207 in 18 cases. In situ hybridization for EBV were negative in all cases.